Wedding expedition, home and travel expenses of Józefa Potocka Ostrowska (1784–1859) - Adamus, Alicja; Studnicka-Mariańczyk, Karolina (In the Mirror of Things, 2022)
This article presents a biography of Józefa Ostrowska, a little-known figure of a dugout. There is no direct biography entirely devoted to Józef Ostrowska in the literature. The authors of the following text set it as their goal to fill the gap by presenting Józefa’s life paths. The second part of the article is an analysis of Józefa’s expenses related to her departure to Warsaw and Józefa’s dowry, which she received when she entered into a marriage with Wojciech Ostrowski. In the opinion of the authors, this analysis may bring the contemporary reader closer to the realities of the nineteenth-century gentry.